Inflation literacy, inflation expectations, and trust in the central bank: A survey experiment - Lena Dräger; Giang Hong Nghiem (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2023)
This paper studies the causal effect of inflation literacy on inflation expectations and trust in the central bank using a randomized control trial (RCT) on a representative sample of the German population. In an experiment with two steps, we first test the effect of non-numerical information about inflation and monetary policy, the extitliteracy treatment. In the second step, we randomly treat respondents with quantitative information and measure whether those who previously received the extitliteracy treatment, incorporate quantitative information differently into their inflation forecasts. We find that the extitliteracy treatment improves respondents' knowledge about monetary policy and inflation and raises their trust in the central bank. It also causes a higher likelihood that respondents provide inflation predictions, but does not affect the level of expected inflation. Similarly, those who received the initial extitliteracy treatment do not react differently to the quantitative information in terms of the level of their inflation forecasts, but they react more strongly to some treatments regarding their reported forecast uncertainty and trust in the central bank.
Keywords: E52; E31; D84; 330; Inflation literacy; inflation expectations; trust in the central bank; survey experiment; randomized control trial (RCT)